Exploration of Literacy and Marketing Strategies of MSMEs: A Conceptual Study Through a Thematic Analysis Approach - sope, Akbar saleh; Sahari, Nur Alvi; Faris, La (UNIVED Press, 2026)
Marketing literacy, which encompasses a holistic understanding of modern marketing concepts and practices, is a critical foundation for MSMEs in Muna Regency to develop effective strategies, particularly in facing digital transformation; this study used a qualitative approach with a reflexive thematic analysis method on purposively selected MSME actors, and the results revealed that the level of marketing literacy is still limited and partial, digital adoption is minimal, and there is a disconnection between local strengths and digital strategy, where marketing literacy proves to function as a crucial mediator in transforming local potential into a competitive advantage, so that its enhancement through contextual policies oriented towards training, infrastructure, and sustainable mentoring is a fundamental prerequisite for increasing MSME competitiveness.